Adaptive active fault-tolerant MPPT control for wind power generation system under partial loss of actuator effectiveness - Wu, Aihua; Zhao, Buhui; Mao, Jingfeng; Wu, Bowen; Yu, Feng (International journal of electrical power & energy systems, 2019)
•An adaptive active fault-tolerant control strategy is proposed to improve work reliability.•A new generalized-perturbation based dynamic model for MPPT control is established.•The control law doesn't require specific information about actuator’s fault pattern or degree.•The control law gains can adaptively adjust by feedback to reduce fault compensation delay.•It ensures a smooth and robust control process whether in actuator normal or fault condition. In order to improve the dynamic performance and reliability of the maximum power point tracking (MPPT), this paper proposes an adaptive active fault-tolerant control (AFTC) strategy of the wind power generation system to overcome uncertain problems, including potential partial loss of actuator effectiveness, unknown modeling errors and external disturbances. The AFTC method is designed according to a new dynamic model of angular speed tracking for wind power generation system based on generalized perturbation. It neither requires the actuator fault information detection, nor relies on the system model parameters and external disturbance identification. In terms of the on-line estimation of the disturbance boundary amplitude and the nonlinear state feedback based on MPPT tracking error, the gain of the switching control is adaptively adjusted to speed up the convergence of the system and reduce the delay of the fault compensation. A first-order integral process is involved in the AFTC law to further weaken the chattering of output signal amplitude, hence smooth the torque and improve the tracking accuracy during generation. In addition, the global stability of the closed-loop control system based on AFTC is proved by the Lyapunov approach. By comparing with the conventional linear PID control and the nonlinear dynamic state feedback control (NDSFC), the case studies simulation results validate the great MPPT fault-tolerant capability even subject to partial loss of actuator effectiveness, and separately show the strong robustness and self-adaptation of the proposed adaptive AFTC method.